Arsenic uptake and speciation in Arabidopsis thaliana under hydroponic conditions. (July 2016) - Park, Jin Hee; Han, Young-Soo; Seong, Hye Jin; Ahn, Joo Sung; Nam, In-Hyun
Abstract: Arsenic (As) uptake and species in Arabidopsis thaliana were evaluated under hydroponic conditions. Plant nutrient solutions were treated with arsenite [As(III)] or arsenate [As(V)], and aqueous As speciation was conducted using a solid phase extraction (SPE) cartridge. Arabidopsis reduced As(V) to As(III) in the nutrient solution, possibly due to root exudates such as organic acids or the efflux of As(III) from plant roots after in vivo reduction of As(V) to As(III). Arsenic uptake by Arabidopsis was associated with increased levels of Ca and Fe, and decreased levels of K in plant tissues. Arsenic in Arabidopsis mainly occurred as As(III), which was coordinated with oxygen and sulfur based on XANES and EXAFS results. The existence of As(III)O and As(III)S in EXAFS indicates partial biotransformation of As(III)O to a sulfur-coordinated form because of limited amount of glutathione in plants. Further understanding the mechanism of As biotransformation in Arabidopsis may help to develop measures that can mitigate As toxicity via genetic engineering. Highlights: Arabidopsis reduced As(V) to As(III) in the nutrient solution. Arsenic uptake by Arabidopsis was associated with increased levels of Ca and Fe. Arsenic in Arabidopsis mainly occurred as As(III) coordinated with O and S. The existence of AsO indicates partial biotransformation of AsO to AsS.